KEBIJAKAN PENDIDIKAN DASAR DALAM PESPEKTIF KEADAILAN DAN PEMERATAAN SD/MI - Herman Herman; Yuliana Ningsih (Fitrah, 2020)
This article aims to discuss the distribution of education in Indonesia. Many factors affect the problem of equal distribution of educational opportunities in Indonesia, for example education is still oriented in urban areas, the number of poor people is quite large, and areas are difficult to access education. Efforts have been made by the government to overcome the problem of equal distribution of educational opportunities, such as making laws and regulations related to equal education, the 9-year compulsory education program, School Operational Assistance (BOS) funds, Bidikmisi and LPDP scholarships, PJJ and KIP programs and SKTM